Zebrafish embryo neonicotinoid developmental neurotoxicity in the FET test and behavioral assays - Hellfeld, Rebecca von; Ovcharova, Viktoriia; Bevan, Samantha; Lazaridi, Maria-Agapi; Bauch, Caroline; Walker, Paul; Bennekou, Susanne Hougaard; Forsby, Anna; Braunbeck, Thomas (Alternatives to animal experimentation, 2022)
The need for reliable, sensitive (developmental) neurotoxicity testing of chemicals has steadily increased. Given the limited capacities for routine testing according to accepted regulatory guidelines, there is potential risk to human health and the environment. Most toxicity studies are based on mammalian test systems, which have been questioned for low sensitivity, limited relevance for humans, and animal welfare considerations. This increased the need for alternative models, one of which is the zebrafish (Danio rerio) embryo. This study assessed selected neonicotinoids at sub-lethal concentrations for their effects on embryonic development and behavior. The fish embryo acute toxicity test (OECD TG 236) determined the lowest observable effect concentrations, which were used as the highest test concentrations in subsequent behavioral assays. In the FET test, no severe compound-induced sublethal effects were seen at <100 µM. In the coiling assay, exposure to ≥1.25 µM nicotine (positive control) affected both the burst duration and burst count per minute, whereas ≥50 µM thiacloprid affected the mean burst duration. Exposure to ≥50 µM acetamiprid and imidacloprid induced significant alterations in both mean burst duration and burst count per minute. In the swimming assay, 100 µM acetamiprid induced alterations in the frequency and extent of movements, whilst nicotine exposure only induced non-significant changes. All behavioral changes could be correlated to findings in mammalian studies. Given the quest for alternative test methods of (developmental) neurotoxicity, integration of zebrafish embryo behavior testing proved beneficial for future tiered testing scheme.
Gesehen am 05.04.2022